Structure Analysis and Forecast of Traditional Chinese Medicine (TCM) Exports to Australia Under the Perspective of Product Segmentation - Ding, Shulin (Pacific International Journal, 2024)
Traditional Chinese medicine (TCM), as a precious treasure of China has played an indispensable role in combating the COVID-19 epidemic, and receiving widespread attention and high regard. The Chinese pharmaceutical industry is gradually on the Road of Revival. However, there are still many bottlenecks restricting internationalization of TCM. How to specifically expand the international market, optimize product structure, and enhance the competitiveness of TCM exports are key and difficult issues. In light of this, this article selects "Australia" as a typical region with a solid foundation for the development of TCM, and innovatively classifies TCM products into four major categories based on its market access policies. By applying STATA to construct an ARIMA model, this study analyzes and forecasts the total export volume of TCM to Australia, the export structure of each category, and the export value for the Q3 2024-Q2 2026 based on data from 2016 to Q2 2024. The results reveal that there is significant potential in the Australian market for the export of TCM. However, the export structure is heavily skewed towards primary products, with the growth rate of high-value-added products being relatively slow. Consequently, it is recommended to increase investment in the research and development of TCM, enhance consumer education to address cultural differences, promote the export of high-value-added products, strengthen the docking of international standards and export certification of products, reinforce brand building and bolster government guidance and talent cultivation to enhance the international competitiveness of the TCM.